Impact of Shading Net on Photovoltaic Cells Performance - Sunanda, Wahri; Gusa, Rika Favoria; Tiandho, Yuant; Pratama, Erick Aryana (Jurnal Teknik Elektro, 2019)
The output of the photovoltaic cells such as voltage and current is an essential parameter to assess the performance of photovoltaic cells. The performance of photovoltaic cells depends on the intensity of solar irradiation and the cleanliness conditions of cells. One of the factors that influence the performance of photovoltaic cells is shading. It can reduce the intensity of solar irradiation on the cells. In this study, the measurement system used two units of current and voltage sensors that simultaneously measures the performance of photovoltaic cells. In photovoltaic cells covered by a shading net with nominal shading rates of 50% and 90%, the average efficiency is 6% and 2% respectively. Meanwhile, for photovoltaic cells without covering by a shading net, the average efficiency is 11%.